Serum midkine level and its association with subclinical coronary artery calcification and carotid atherosclerosis in chronic kidney disease - Osama Nady Mohamed; Marwa Ibrahim Mohamed; Shaimaa F. Kamel; Ahmed M. Dardeer; Sayed Shehata; Hassan MH Mohammed; Asmaa Khalf Kamel; Doaa Elzaeem Ismail; Nehal I. Abbas; Mohamed Ahmed Abdelsamie; Ahmed Fathy Kamel Ziady; Manar M. Sayed; et al. (BMC Nephrology)
Abstract Background There are no studies investigating the role of midkine (MK) in vascular calcification (VC) or vascular disease associated with chronic kidney disease (CKD). This study assessed serum MK level and investigated its relationship with carotid atherosclerosis and coronary artery calcification (CAC) in non-dialysis CKD. Methods The study comprised 80 controls and 185 adult patients with CKD at stages 3–5 who were free of cardiovascular diseases. Acute renal failure, chronic hemodialysis, severe liver disease, inflammatory states, anticoagulation therapy and cancer were excluded. The patients were classified based on presence of CAC score into severe and mild to moderate CAC groups. They were also divided into atherosclerotic and non-atherosclerotic groups based on carotid atherosclerosis. CBC, kidney function tests, lipid profile, intact parathyroid hormone (iPTH), and phosphorus were assessed. Serum levels of MK, tumor necrosis factor- α (TNF- α), interleukin-6 (IL-6), and high-sensitivity C-reactive protein (hs-CRP) were quantitatively tested using ELISA. Cardiac CT scan was done to calculate CAC score. Carotid ultrasonography was used to evaluate carotid intima media thickness (CIMT) and identify plaques. Results All CKD categories, including CKD-3, CKD-4, and CKD-5, showed higher rates of carotid plaques (p = 0.007, p < 0.001, and p < 0.001, respectively), higher levels of MK (p < 0.001 for each), and higher CAC scores (p < 0.001 for each) as CKD worsened. Compared to mild to moderate CAC patients, severe CAC patients showed increased CIMT (p < 0.001) and raised serum levels of MK (p < 0.001), TNF-α (p = 0.001), IL-6 (p = 0.002), hs-CRP (p = 0.003), iPTH (p = 0.02), phosphorus (p < 0.001), total cholesterol (TC), and low density lipoprotein-cholesterol (LDL-C). Multivariate linear regression revealed that CAC was reliably predicted by MK (p = 0.008) and serum creatinine (p = 0.001). Carotid atherosclerotic patients had higher serum levels of MK, TNF-α, IL-6, hs-CRP, iPTH, phosphorus, TC, total triglycerides and LDL-C (p < 0.001 for each). Multivariate logistic regression showed that serum MK (p = 0.001), serum creatinine (p = 0.005), age (p < 0.001), iPTH (p = 0.007), and IL-6 (p = 0.024) were significant predictors of carotid atherosclerosis. Conclusions As CKD worsened, MK levels, carotid atherosclerosis and CAC increased. Serum MK was a reliable biomarker for asymptomatic carotid atherosclerosis and CAC in non-dialysis CKD, allowing prompt early diagnosis to avert cardiovascular morbidity and death in the future. Trial registration The trial number was 1138 and its registration was approved by the hospital’s Research Ethics Committee in 4/2024.